Searching for a new dynamic of industrialization and urbanization: anatomy of China's characteristic town program. Issue 7 (9th August 2018) - Zou, Yonghua; Zhao, Wanxia
ABSTRACT: The characteristic town program is one of China's latest industrialization and urbanization strategies. Originating in Zhejiang, characteristic towns are expected to serve as platforms for industrial upgrading and the promotion urbanization. This paper attempts to analyze the characteristic town program by examining the reasons behind the origination of characteristic towns, as well as elucidating the towns' components. The paper argues that this exploratory local program has been leveraged into a national-level strategy because the primary idea underlying characteristic towns has been in accordance with several of China's critical policies. Furthermore, the paper presents the challenges that the characteristic town program has encountered. The characteristic town program can be viewed as a new effort of entrepreneurial governments and a spatial fix for capital during the period of industrial upgrading. This paper helps us to better understand one of China's explorations in searching for a new dynamic of industrialization and urbanization.